2014
DOI: 10.1007/s00701-014-2103-z
|View full text |Cite
|
Sign up to set email alerts
|

The variability of atlas-based targets in relation to surrounding major fibre tracts in thalamic deep brain stimulation

Abstract: We found a considerable variability of the location of atlas-based target points of the ventralis intermedius nucleus in relation to neighbouring major fibre tracts in individual patients. These results suggest that individualised targeting to structures not directly visible on conventional MRI is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 28 publications
2
46
0
Order By: Relevance
“…We fully agree with the concerns regarding the limitations of tractography, as already discussed in our article [1] and earlier reports by our group [2,6,10]. His own work constitutes a further valuable contribution to the topic [3].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…We fully agree with the concerns regarding the limitations of tractography, as already discussed in our article [1] and earlier reports by our group [2,6,10]. His own work constitutes a further valuable contribution to the topic [3].…”
supporting
confidence: 87%
“…Dear Editor, We would like to thank Josue M. Avecillas-Chasin for his appreciation of our study BThe variability of atlas-based targets in relation to surrounding major fibre tracts in thalamic deep brain stimulation^ [1] and for his valuable comments on the study.…”
mentioning
confidence: 99%
“…We do not think so. Even with our standardized protocol we observed a significant variability in the course of the detected fiber tracts between left and right hemispheres and between different patients . The resolution of fibertracking is limited in areas of the brain where fibers of different functional tracts are getting in close contact or even cross each other.…”
Section: Discussionmentioning
confidence: 79%
“…Overall, the T‐VIM target is more lateral and anterior than the conventional targeting method. Anthofer and colleagues recently compared the atlas‐based VIM target with the location of the DRT (as determined by deterministic tractography) in a cohort of tremor patients . They concluded that the optimal site for DBS implantation was more lateral than the planned atlas‐based trajectory.…”
Section: Discussionmentioning
confidence: 99%